Predictors of annual membership renewal to increase the sustainability of the Nepal National Health Insurance program: A cross-sectional survey. - Gaj Bahadur Gurung; Alessio Panza (Public Library of Science (PLoS), 2022)
Expanding membership coverage and retention of the National Health Insurance (NHI) programs among informal sector workers (ISWs) continues to be a significant challenge in most low and lower-middle-income countries (LMICs). The Nepal NHI program is also facing a similar problem, but to date, there are no studies that focus on identifying key predictors of annual membership renewal and retention in Nepal. This study therefore aimed to determine the predictors of intention to renew annual subscription to the NHI program among enrolled members. This cross-sectional quantitative study was part of a larger mixed-methods study conducted in three districts in Nepal. A random sample of 182 current NHI members and 61 dropped out NHI members who met the inclusion criteria were interviewed. The study's dependent variable was the intention to renew annual membership and employed univariate regression to assess the bivariate associations with the independent variables. The multivariate logistic regression examined the net effect of the independent variables on the odds of intention to renew. Our results showed that the household (HH) with high monthly income had lower odds of renewing their annual NHI membership (adjusted OR: 0.14, 95% CI: 0.03-0.58). Similarly, households (HHs) with overall health service satisfaction (adjusted OR:3.59, 95%CI: 1.23-10.43) and increased frequency of visits after NHI membership (adjusted OR: 10.09, 95% CI: 1.39-73.28) had high odds of renewing their membership. The top three dropout reasons were health services underutilization (43.3%), poor health services (26.9%), and the inadequacy of the benefits package (14.9%). Almost 64% of the respondents were willing to renew their membership upon improved services. The study found that the Nepal NHI annual membership renewal key predictors are HH income, health service quality, and health service utilization. Among these three key predictors, health service quality and service utilization were among the top three dropout reasons. The study, however, did not differentiate between moral hazards or actual service utilization, demanding further studies on the health service utilization of the insured members.